Tiktok Sebagai Media Sosial dalam Melakukan Kritik terhadap Pembangunan di Lampung - Firdaus, Satria; Naila, Neysa; Pramesti, Azzahra Dinar; Sari, Cindy Kartika; Azzahra, Dhara Fatimah; Angela, Deni (Indonesian Journal Publisher, 2023)
In TikTok, as one of the most popular social media platforms, has changed the paradigm of communication and has become a source of information for today's society. In this context, TikTok content creators, such as Bima Yudho, have used this platform to convey criticism of the development of Lampung Province. However, the use of TikTok to convey criticism also carries risks, as experienced by Bima Yudho who was reported to the authorities regarding violations of the Information and Electronic Transactions (ITE) Law. In this article, the author uses a qualitative research method by means of a literature review and looking for previous sources. The purpose of this research is to find out how TikTok as a social media can be a tool to criticize development in Lampung. The results and discussion of this research are that it can be said that TikTok users show their activeness in conveying critical opinions on development in Lampung by using their creativity and skills in using TikTok features to voice their views and participate in public debates on relevant development issues.